2014
DOI: 10.1093/nar/gku757
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, properties, and biological activity of boranophosphate analogs of the mRNA cap: versatile tools for manipulation of therapeutically relevant cap-dependent processes

Abstract: Modified mRNA cap analogs aid in the study of mRNA-related processes and may enable creation of novel therapeutic interventions. We report the synthesis and properties of 11 dinucleotide cap analogs bearing a single boranophosphate modification at either the α-, β- or γ-position of the 5′,5′-triphosphate chain. The compounds can potentially serve either as inhibitors of translation in cancer cells or reagents for increasing expression of therapeutic proteins in vivo from exogenous mRNAs. The BH3-analogs were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 65 publications
4
56
0
Order By: Relevance
“…Our data suggest that 12b competes for the active site of Dcp2 and may act as a tightly bound mimic of the 5 ′ cap, paving the way for future structural studies and the development of potent, selective inhibitors of Dcp2. Observations made during our initial screening of the synthetic nucleotide library for Dcp2 inhibition are consistent with earlier reports concerning the influences of structural alterations of nucleotide phosphate chains on cap-protein interactions (Kowalska et al 2008(Kowalska et al , 2014Rydzik et al 2012). We find that the introduction of charge-retaining nonbridging modifications (S − , BH 3 − ) into cap analogs seemed to generally have higher impact on Dcp2 decapping activity than the bridging (CH 2 and NH) modifications.…”
Section: Discussionsupporting
confidence: 90%
“…Our data suggest that 12b competes for the active site of Dcp2 and may act as a tightly bound mimic of the 5 ′ cap, paving the way for future structural studies and the development of potent, selective inhibitors of Dcp2. Observations made during our initial screening of the synthetic nucleotide library for Dcp2 inhibition are consistent with earlier reports concerning the influences of structural alterations of nucleotide phosphate chains on cap-protein interactions (Kowalska et al 2008(Kowalska et al , 2014Rydzik et al 2012). We find that the introduction of charge-retaining nonbridging modifications (S − , BH 3 − ) into cap analogs seemed to generally have higher impact on Dcp2 decapping activity than the bridging (CH 2 and NH) modifications.…”
Section: Discussionsupporting
confidence: 90%
“…Such an approach provides a relatively simple way to obtain a wide scope of chemically modified oligophosphate mono-and diesters (Fig. 7), including phosphorothioates [79][80][81], seleno- [82], borano- [83], and fluorophosphates [84], as well as phosphoramidates [85], C-phosphonates [86], and bisphosphonates [87]. P-imidazolides were shown to react readily with other inorganic nucleophiles such as fluorides [84] and sulfates [88] to yield fluorophosphates and phosphosulfates, respectively.…”
Section: Synthesis Of Rna Caps: P-imidazolides and MCL 2 -Mediated Comentioning
confidence: 99%
“…The first analogs, which combined these two features, were compounds carrying a non-bridging O-S substitution at the beta position of the triphosphate chain, referred to as b-S-ARCAs [108]. Later, it was found that similar properties could be conferred to mRNA by an O-to-BH 3 substitution [65,83]. Recent studies have shown that applying two O-S substitutions at two adjacent phosphate moieties in a tri-or tetraphosphate bridge may provide biological properties superior to b-S-ARCA [81].…”
Section: Mrna Modification With Synthetic Cap Analogs (Transcription mentioning
confidence: 99%
“…5, 6 We have recently shown that some chemical modifications of the oligophosphate chain within the cap structure can increase the affinity to eIF4E and confer resistance towards DcpS. 1,[7][8][9] For instance, replacement of one of the c-oxygens in m 7 Gp c p b p a G or a-oxygens in m 7 GTP with either BH 3 or S generally stabilises the complex with eIF4E 10,11 and significantly decreases susceptibility to hydrolysis by DcpS. Inhibition studies in RRL (Rabbit Reticulocyte Lysate) have shown that a combination of these two features results in compounds that are potent and stable inhibitors of cap-dependent translation.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition studies in RRL (Rabbit Reticulocyte Lysate) have shown that a combination of these two features results in compounds that are potent and stable inhibitors of cap-dependent translation. 8,[10][11][12] In contrast to mononucleotide cap analogues, dinucleotide analogues can be incorporated in vitro into mRNA by bacterial 13 or viral 14 RNA polymerases. Such capped transcripts can find applications in biochemistry and gene therapy.…”
Section: Introductionmentioning
confidence: 99%